Hot flushes and night sweats symptom profiles over a 17-year period in mid-aged women: The role of hysterectomy with ovarian conservation. (September 2016) - Wilson, Louise F.; Pandeya, Nirmala; Byles, Julie; Mishra, Gita D.
Highlights: There has been limited longitudinal analysis of hysterectomy and vasomotor symptoms. The present study found that hysterectomy with ovarian conservation is associated with persistent hot flushes and night sweats. Obesity, smoking and a lower level of education/occupation are also associated with persistent symptoms. Abstract: Objectives: There is limited research on hot flushes and night sweats in women with a hysterectomy with ovarian conservation. We aimed to describe the patterns of these symptoms in a cohort of Australian women and to investigate the relationship between distinct symptom patterns and hysterectomy status. Study design and outcome measures: Repeated-measures latent class analysis (LCA) was used to identify hot flushes and night sweats symptom patterns across seven surveys (over 17 years) in the mid-cohort of the Australian Longitudinal Study on Women's Health. Multinomial logistic regression was used to assess the associations of the symptom patterns in women with a hysterectomy with ovarian conservation (n = 1129) versus women without a hysterectomy (n = 4977). Results: A higher proportion of women with a hysterectomy than of those without experienced a constant pattern of hot flushes (15% versus 30%) and night sweats (9% versus 19%). Women with a hysterectomy had higher odds of constant hot flushes versus minimal hot flushes (OR = 1.97, 95% CI: 1.64, 2.35) and constant versus minimal night sweats (OR = 2.09, 95% CI: 1.70, 2.55). Smoking, a 'lower level of education to non-professional occupation' pathway and body mass index (BMI) patterns of 'always obese' and 'increasingly obese' were also associated with a higher risk of constant symptoms. Conclusions: Women who have a hysterectomy (with ovarian conservation) have a higher risk of hot flushes and night sweats that persist over an extended period.